Trip report : rapid rural appraisal in Maranhao Brazil to classify small farmer rice agroecosystems, Jan. 16-Feb. 13, 1990 - Robison, DM (International Center for Tropical Agriculture, 1990)
Over a period of four weeks a survey was conducted with cooperation of CNPAF and EMAPA (Empresa Maranhense de Pesquisa Agropecuaria). We spent 23 days in the field, travelled 7000 km and surveyed 44 rice producing communities spread though different Agroecological zones in the state. In each community we met with 5-30 producers and held informal interviews of around 2 hours. All communties declared farming the most important activity and rice or cassava the most important crop. Significant variation exists between the cropping systems and the problems that were identified as the most important. The survey showed that the are four distinct manual rice production systems in Maranhao. The overwhelming impression over much of the state is of uncontrolled deforestation since 1950 and the subsequent concentration of land in large cattle ranches